Analysis of Creative and Collaborative Thinking Abilities on Animalia Material in Class X Students of SMA Negeri 1 Airmadidi - Josua Gigir; Carolin Manuahe; Decky W. Kamagi (International Forum of Researchers and Lecturers, 2024)
Biology learning demands learning competencies in the realm of high-level understanding, so many students find it challenging to develop their critical thinking skills and, therefore, have difficulty completing various concepts in biology. For this reason, a particular way of learning is needed so that it fosters students' critical thinking skills through creative and collaborative thinking skills so that they can be well-honed in order to be able to solve various complex concepts in biology. Therefore, this research aims to determine the creative and collaborative thinking abilities of class X SMA Negeri 1 Airmadidi students on Animalia material, focusing on their creative and collaborative thinking abilities. This type of qualitative research describes data obtained from a rubric containing research indicators. The research results show that the profile of students' creative and collaborative skills shows good development based on the indicators obtained. Indicators of creative and collaborative thinking abilities are at scores 3 and 4, which shows that students can give excellent and precise answers to both questions through discussions and written tests. Based on these results, the analysis of creative and collaborative thinking abilities in class X12 students at SMA Negeri 1 Airmadidi is in good ability results.